The Metaphysics of Shared Action: an analysis based on the idea of commitments - Chaves, Thiago Monteiro (Intuitio, 2017)
Abstract: In this paper I consider two examples of social interaction and try to figure out what is distinctive of each example by pursuing an examination of the nature of the commitments present in each situation. I discuss the ideas of pre-commitment and joint commitment and pursue an understanding of their roles in joint or shared action. The main argument of the paper is that the metaphysics of shared action is better understood through the proper kind of commitments that are constitutive of the action. commitments; joint action; agreements; social contract; convention.